2014
DOI: 10.3846/13923730.2014.941922
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Electrical Capacitance and Electrical Conductivity of Char Resulting From Natural and Treated Wood

Abstract: Abstract. Wood is a material widely used for construction purposes and having quite a number of advantages. However, one of the major drawbacks of wood are its flammability. in case of fire in wooden buildings or constructions made of timber structures, the most noticeable feature of combustion is charring these structures. this property is important for identifying the cause of a fire. therefore, it is necessary to relate charring timber structures with certain significant effects of fire such as its duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Conversely, if timber has not been impregnated before a fire, the electrical conductivity will be < 0.1 mS/cm. The electrical conductivity of a medium made up of impregnated charcoal and distilled water varies insignificantly when heating the timber for 30 minutes or longer, and the lowest value was 0.1 mS/cm, regardless of the type, output and extinguishing method of the flame-retardant solution used in Lithuania (Mačiulaitis et al 2015).…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, if timber has not been impregnated before a fire, the electrical conductivity will be < 0.1 mS/cm. The electrical conductivity of a medium made up of impregnated charcoal and distilled water varies insignificantly when heating the timber for 30 minutes or longer, and the lowest value was 0.1 mS/cm, regardless of the type, output and extinguishing method of the flame-retardant solution used in Lithuania (Mačiulaitis et al 2015).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The composition of the medium was 50 g of distilled water and 0.1 g of the dispersed testing material (Mačiulaitis et al 2015).…”
Section: Determination Of Electrical Capacity Of Carbonmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the electrical conductivity of the solution no longer significantly increased with time and stabilized around 80~100 µs/cm in the eighth cycle, indicating that the soluble salt ions in the wood were no longer migrating noticeably. Comparing this conductivity with that of the cold water extract of pine wood, which ranges from 60~180 µs/cm [27,28], it can be concluded that most of the soluble salts in the wood had been successfully removed, and the extraction of iron sulfides could be implemented. Therefore, the electrical conductivity of the solution no longer significantly increased with time and stabilized around 80~100 µs/cm in the eighth cycle, indicating that the soluble salt ions in the wood were no longer migrating noticeably.…”
Section: Extraction Of Soluble Saltsmentioning
confidence: 96%